The effect of liquidity and leverage on financial performance with company size as a moderating variable: A study on companies listed in Jakarta Islamic Index 30 - Cahyani, Fatma Intan; Santoso, Suryo Budi; Hariyanto, Eko; Setyadi, Edi Joko (Universitas Islam Indonesia, 2024)
IntroductionThe Jakarta Islamic Index is an index on the Indonesia Stock Exchange which contains companies that contribute to the halal industry in Indonesia. However, research on financial performance specifically using liquidity, leverage and company size is still limited.ObjectivesThe research aims to examine the effect of liquidity and leverage on performance financial with company size as a moderating variable. This research aims to find out which companies in the Jakarta Islamic Index 30 are influenced by factors that can improve their financial performance so that they have a more positive impact on companies and investors.MethodThe subject of this research companies listed on Jakarta Islamic Index 30 for 2020 – 2022. Data collection techniques used in this study were purposive sampling and with a sample size of 114 samples. While the data analysis techniques used in this study is classic multiple regression analysis with interaction.ResultsThe analysis show that liquidity has a significant effect on financial performance, leverage has no effect on financial performance, company size moderates liquidity on financial performance but does not moderate leverage to financial performance.ImplicationsCompanies registered on Jakarta Islamic Index 30 can utilize their debt policy to obtain additional capital as long as the use is reasonable and does not burden the company.Originality/NoveltyThis study contributes to broaden the knowledge on financial performance of companies listed in Jakarta Islamic Index 30.